The mechanism of action and manifestation of toxic effects of heavy metals on an organism (the literature review) - Konkabaeva, А.Е.; Baranova, T.N.; Ishmuratova, М.Yu. (Fundamental and Experimental Biology, 2016)
The literary review containing data on the main sources of intake of heavy metals in objects of environment and in an organism is presented in article. The characteristic of the term «heavy metals» is given to, the elements getting to group of heavy metals are defined the biological role and participation of heavy metals in biological processes is opened. Toxic properties of heavy metals, sources and ways of receipt them in an organism are lit. Besides, in article the general principles of impact of separate metals on an organism, and also their mechanisms are considered. The main attention is paid to toxic effect of lead, cadmium and copper on an organism.